ASMesh: Anonymous and Secure Messaging in Mesh Networks Using Stronger, Anonymous Double Ratchet - Bienstock, Alexander; Rösler, Paul; Tang, Yi (CCS '23 - Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security, 2023)
The majority of secure messengers have single, centralized service providers that relay ciphertexts between users to enable asynchronous communication. However, in some scenarios such as mass protests in censored networks, relying on a centralized provider is fatal. Mesh messengers attempt to solve this problem by building ad hoc networks in which user clients perform the ciphertext-relaying task. Yet, recent analyses of widely deployed mesh messengers discover severe security weaknesses (Albrecht et al. CT-RSA'21 & USENIX Security'22). To support the design of secure mesh messengers, we provide a new, more complete security model for mesh messaging. Our model captures forward and post-compromise security, as well as forward and post-compromise anonymity, both of which are especially important in this setting. We also identify novel, stronger confidentiality goals that can be achieved due to the special characteristics of mesh networks (e.g., delayed communication, distributed network and adversary). Finally, we develop a new protocol, called ASMesh, that provably satisfies these security goals. For this, we revisit Signal's Double Ratchet and propose non-trivial enhancements. On top of that, we add a mechanism that provides forward and post-compromise anonymity. Thus, our protocol efficiently provides strong confidentiality and anonymity under past and future user corruptions. Most of our results are also applicable to traditional messaging. We prove security of our protocols and evaluate their performance in simulated mesh networks. Finally, we develop a proof of concept implementation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Anonymity; Double Ratchet; Forward Security; Mesh Network; Post-Compromise Security; Secure Messaging